Safety, Tolerability, and Immunogenicity of an mRNA-Based Respiratory Syncytial Virus Vaccine in Healthy Young Adults in a Phase 1 Clinical Trial - Shaw, Christine A; Mithani, Runa; Kapoor, Archana; Dhar, Rakesh; Wilson, Lauren; El Asmar, Laila; Schnyder-Ghamloush, Sabine; Schaefers, Kristi; August, Allison; Stoszek, Sonia K; Chen, Grace L (The Journal of infectious diseases, 2024)
Abstract Background Respiratory syncytial virus (RSV) presents a global health concern. A lipid nanoparticle–encapsulated mRNA-based RSV vaccine (mRNA-1345) that encodes the membrane-anchored RSV prefusion–stabilized F glycoprotein is under clinical investigation. Methods This phase 1 dose escalation study was based on a randomized, observer-blind, placebo-controlled design, and it assessed the safety and immunogenicity of mRNA-1345 in healthy adults aged 18 to 49 years. Participants were randomized to receive 1 dose of mRNA-1345 (50, 100, or 200 µg) or placebo or 3 doses of mRNA-1345 (100 µg) or placebo 56 days apart. Results mRNA-1345 was well tolerated at all dose levels. The most common solicited adverse reactions were pain, headache, fatigue, myalgia, or chills, which were all generally mild to moderate. At 1 month postinjection, a single injection of mRNA-1345 boosted RSV neutralizing antibody titers (geometric mean fold rise: RSV-A, 20.0–23.5; RSV-B, 11.7–16.0) and RSV prefusion binding antibody concentrations (geometric mean fold rise, 16.1–21.8), with no apparent dose response. Antibody levels remained above baseline through 6 months. Sequential doses of 100 µg were well tolerated but did not further boost antibody levels. Conclusions A single mRNA-1345 injection demonstrated an acceptable safety profile in younger adults and induced a durable neutralizing antibody response, supporting its continued development. Clinical Trials Registration ClinicalTrials.gov NCT04528719. Respiratory syncytial virus presents a global health concern. We assessed the safety and immunogenicity of an mRNA-based vaccine, mRNA-1345, in healthy adults aged 18 to 49 years. mRNA-1345 vaccine was well tolerated and immunogenic in younger adults.